Guest - Mitali Meelan; MEELAN (Mitali) (New Delhi Black Ink, 2016)
Eighteen-year-old Neha Ranade is perfectly content with her life$1 (Ba singer boyfriend, a group of loyal friends and with the college annual festival around the corner, her days are full and exciting. But when her father$1 (Bs Canadian colleague arrives home, Neha$1 (Bs grand plans are uprooted. What could be the intentions of this curious guest$1 (Bs sudden visit$1 (Bfor better or for worse?s
Keywords: Indian English Fiction; Indian English Literature